Duration of breastfeeding in preterm infants followed at a secondary referral service - Brunnella Alcantara Chagas de Freitas; Luciana Moreira Lima; Carla Fernanda Lisboa Valente Carlos; Silvia Eloiza Priore; Sylvia do Carmo Castro Franceschini (Sociedade de Pediatria de São Paulo, 2016)
Abstract Objective: Identify and analyze variables associated with shorter duration of breastfeeding in preterm infants. Methods: Retrospective cohort of premature infants followed up at secondary referral service in the period of 2010-2015. Inclusion: first appointment in the first month of corrected age and have undergone three or more consultations. Exclusion: diseases that impaired oral feeding. Outcome: duration of breastfeeding. A total of 103 preterm infants were evaluated, accounting for 28.8% of the preterm infants born in the municipality in that period, with a power of study of 80%. Descriptive analysis, t-test, chi-square test, Kaplan-Meier curves and Cox regression were used. p-values <0.05 were considered significant. Results: The median duration of breastfeeding among preterm infants was 5.0 months. The risk of breastfeeding discontinuation among preterm infants with gestational age <32 weeks was 2.6-fold higher than for those born at 32 weeks or more and the risk of breastfeeding interruption in preterm infants who were receiving breastfeeding supplementation in the first outpatient visit was 3-fold higher when compared to those who were exclusively breastfed in the first consultation. Conclusions: The median duration of breastfeeding in preterm infants was below the recommended one and discontinuation was associated with gestational <32 weeks and the fact that the infant was no longer receiving exclusive breastfeeding in the first outpatient visit. When these two variables were associated, their negative effect on the median duration of breastfeeding was potentiated.